2013
DOI: 10.1089/aid.2012.0298
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Near Full-Length HIV Type 1 Genomic Sequences from 21 Korean Individuals

Abstract: The Korean subclade of subtype B (KSB) is the most prevalent HIV-1 strain found in Korea. To date, only two near full-length HIV-1 sequences from Korean patients have been reported. Here, we analyzed a total of 24 near full-length genomes of HIV-1 strains that were isolated from 17 antiretroviral therapy (ART)-naive patients and four ART-exposed patients. Proviral DNA from peripheral blood mononuclear cells was PCR amplified and directly sequenced. Phylogenetic analyses were used to classify viruses from 19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In total, 251 HIV-1-infected patients were diagnosed in Korea before 1992. Based on epidemiological data, it appears that 105 patients were domestically infected with KSB, the transmission of which began in 1988 [1,2,13,14], and 40 patients were infected with Western subtype B. There were no samples from about 20 people, and researchers could therefore not determine their HIV-1 subtype.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 251 HIV-1-infected patients were diagnosed in Korea before 1992. Based on epidemiological data, it appears that 105 patients were domestically infected with KSB, the transmission of which began in 1988 [1,2,13,14], and 40 patients were infected with Western subtype B. There were no samples from about 20 people, and researchers could therefore not determine their HIV-1 subtype.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there was a significant inverse correlation found between KRG and the annual decrease of CD4+ T cells and between KRG and RNA copy number in our previous study [22] . Furthermore, we reported that, in addition to clinically beneficial effects, a high frequency of genetic defects, including gΔ nef [5] , [6] , [22] , [23] , [24] , [25] , are associated with the long-term intake of KRG [26] . Consequently, we reported many long-term slow progressors (LTSPs) among a small Korean cohort of HIV-1 patients who have taken KRG for more than 10 yr [26] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we reported that, in addition to clinically beneficial effects, a high frequency of genetic defects, including gΔ nef [5] , [6] , [22] , [23] , [24] , [25] , are associated with the long-term intake of KRG [26] . Consequently, we reported many long-term slow progressors (LTSPs) among a small Korean cohort of HIV-1 patients who have taken KRG for more than 10 yr [26] . Among the LTSPs, two patients have remained healthy for 26 yr after diagnosis in the absence of ART [26] , [27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 100 HIV-1 subtype B genomes and 50 HIV-1 non-subtype B genomes were randomly pulled (with no duplicates) from the Los Alamos HIV Database (LANL; ) reference genome 2017 list ( Table S1 ; [ 16 , 28 , 40 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , …”
Section: Methodsmentioning
confidence: 99%